ธรณีวิทยาแผ่นดินไหวของกลุ่มรอยเลื่อนแม่จัน ภาคเหนือประเทศไทย - รัชนก นาสมทรง (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
In this study, the earthquake geology, i.e., paleoseismology, is investigated carefully along the Mae Chan fault zone. The orientation of fault and the adjacent areas are interpreted using the Satellite image. Geomorphological evidences are also investigated in order to delineate the fault trace. Based mainly on remote sensing interpretation, various geomorphological feature indicating fault are revealed, e.g., triangular facets and sag pond. Among a number of outcrops exposed along the Mae Chan fault, a prominent site showing earthquake faulting in the sedimentary profile, at Ban I Ko Pa Bong Ngam Lang, Mae Chan district. Five sedimentary samples are decided to collect in order to date of earthquake faulting. According to Thermoluminescence dating, it is indicated that the earthquake faulting is posed at 34,900 year ago defining as the potential active fault.